G-quadruplex aptamers for cervical cancer therapy - Carvalho, Josué Leandro de Oliveira e (2020)
Annually, more than 500,000 new cervical cancer cases are diagnosed worldwide with a 60% mortality rate. In Portugal, about 750 new cases are annually diagnosed which in 2018 resulted in 340 deaths. Human papillomaviruses (HPVs) are the principal cause for the development of cervical cancer. High-risk HPV types 16 and 18 are responsible for 70% of all cases. Persistent HPV infection leads to the hyperproliferation of the infected cells by downregulating epithelial differentiation, epidermal development, and innate immune responses. The oncogenic potential of high-risk HPV types is attributed to the expression of oncoproteins, E6 and E7, which inactivate tumour suppressor p53 and members of retinoblastoma family, leading to carcinoma development. Despite recent progresses in screening and HPV vaccination that reduced cervical cancer incidence, treatment options for women with persistent HPV infection or in its latent form are still missing. Furthermore, the available therapeutic options for cervical cancer have limited effectiveness and specificity, causing great pain to patients, and do not benefit from the research addressing the host-HPV interaction patterns during malignant progression. The genome of HPV is divided into 3 regions: a long control region (LCR) that contains cis-elements necessary for the replication and transcription of viral DNA; the early region, composed of six open reading frames (ORFs) labelled E1−E7, and a late region with two ORFs coding for capsid structural proteins L1 and L2. Recently, several guanine-rich regions have been found in the genome of ten HPV types (both high- and low-risk), and the potential of the sequences to fold into stable G-quadruplex (G4) structures was demonstrated. These guanine-rich regions are present in LCR, E1, E4 regions and L2 protein coding sequence, which are involved in transcription, replication, and viral proteins production. Hence, targeting these G-rich regions of the HPV genome could serve as a potential antiviral strategy, using small ligands that can stabilize the viral G4 regions and regulate gene expression. Nucleolin is overexpressed in the surface of cervical cancer cells and was shown to be involved in the activation of HPV18 oncogene transcription in cervical cancer and to be related with HPV16 genome stability maintenance. Nucleolin is present in the nucleus, cytoplasm, and cell surface. The roles of cell-surface nucleolin in tumorigenesis, angiogenesis, and cancer signalling pathways have also been described. Therefore, nucleolin is an attractive target for the development of targeted therapies for both cervical cancer and HPV infection given its high abundance, its multifaceted influence on oncogenesis and virulence of HPV, and its selective presence on the plasma membrane of cancer cells, but not on untransformed, normal cells. AS1411 is a nucleolin-targeted G4 aptamer with antitumoral effect in many cancers that has also been extensively used for the tumour-specific delivery of both therapeutic and imaging agents. This thesis innovates by proposing the development of aptamer-based carriers of antiviral/anticancer G4 ligands as a new therapeutic strategy for HPV infection and cervical cancer. Firstly, several G4-specific ligands belonging to different aromatic scaffolds such as indole, phenanthroline and acridine, were synthesized and characterized for their ability to bind G4 structures, either found in the cancer cell genome (oncogene promoter and telomeric G4s) or the HPV genome. Their effect in inhibiting key G4-dependent processes was demonstrated by their potential to inhibit Pif1 helicase and Taq polymerase enzymes, and to downregulate c-MYC oncogene expression. The ligands demonstrated interesting antitumoral effects in cervical cancer cell lines, particularly ligand C8, which was also found to inhibit HPV18 replication and encapsidation in organotypic raft cultures, with resulting antiproliferative effects in infected tissue. Having established the ability of the ligands as anticancer/antiviral agents, the development of an aptamer-based delivery system was envisioned. AS1411 aptamer and its derivatives AT11, AT11-L0 and AT11-B0 were used to selectively convey the G4 ligands to HPV-positive cervical cancer cells, with a simple non-covalent conjugation strategy and mediated by cell-surface nucleolin recognition. This strategy proved to be efficient at accumulating the ligands in cervical cancer cells, improving their antitumoral effect while limiting their off-target toxicity towards normal cells. Interestingly, because the used aptamers are also G4-forming sequences, the presence of the G4 ligands improved the aptamers’ properties such as cellular penetration and serum nuclease resistance, without affecting nucleolin recognition. Finally, advanced and intricate drug delivery systems were developed aiming at enhancing the clinical applicability of the anticancer/antiviral agents. AS1411-decorated nanoaggregates were synthesized to encapsulate the G4 ligands, allowing their sustained and targeted release within HPV-positive cells in precancerous and cancerous stages. The nanoaggregates presented small sizes (nanoscale), negative surface charge, stability, and a suitable drug release profile. The presence of AS1411 on the nanoaggregates surface as a cancer-specific guiding agent promoted the specific accumulation of the G4 ligands in cervical cancer cells which inhibited their growth, with little effect on non-malignant normal cells. The nanoaggregates were also able to penetrate cervix tissue biopsies of patients with HPV infection in precancerous stages, demonstrating the potential of this system to treat HPV infection in its latent stage, preventing oncogenesis and cervical cancer progression. The administration route of the drug-loaded nanosystems was also addressed. The C8-loaded nanoaggregates were formulated as a gel for local application in the female genital tract, specifically tissue with precancerous lesions and/or HPV infection. Preliminary ex vivo permeation studies using porcine vaginal tissue demonstrated the efficacy of the formulation in penetrating and accumulating the nanosystems in the target cells. Overall, the research performed throughout this doctoral thesis defined improvements in the design of G4-specific compounds with dual anticancer/antiviral effects and led to the discovery of potential aptamer-based delivery systems for G4 ligands. The original results obtained during the past years provide important knowledge in the applicability of G4 nucleic acids for the development of specific and effective therapeutics against HPV virulence and oncogenesis. Furthermore, the encouraging pre-clinical evaluation performed on the newly developed nanomedicines demonstrated the need of continuing the research initiated by this project, particularly by pursuing the in vivo studies to verify the clinical applicability of these systems. In the future, a similar strategy could be extended to the treatment of other types of cancers (for instance HPV-induced oropharyngeal cancers) and other viral infections such as HIV, hepatitis virus and SARS-CoV-2.